2019
DOI: 10.3390/s19153277
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Elements in Fertilizer Using Laser-Induced Breakdown Spectroscopy Coupled with Support Vector Regression Model

Abstract: The rapid detection of the elements nitrogen (N), phosphorus (P), and potassium (K) is beneficial to the control of the compound fertilizer production process, and it is of great significance in the fertilizer industry. The aim of this work was to compare the detection ability of laser-induced breakdown spectroscopy (LIBS) coupled with support vector regression (SVR) and obtain an accurate and reliable method for the rapid detection of all three elements. A total of 58 fertilizer samples were provided by Anhui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The LSSVM is a machine learning method which combinates least square and support vector machine (SVM). In this paper, the LSSVM algorithm deformed the optimization formula of SVM by using the formula of least squares 22‐30 …”
Section: Experiments and Methodsmentioning
confidence: 99%
“…The LSSVM is a machine learning method which combinates least square and support vector machine (SVM). In this paper, the LSSVM algorithm deformed the optimization formula of SVM by using the formula of least squares 22‐30 …”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Wang et al (2018) evaluated the nitrogen fertilizer levels of a tea plant using visible and near-infrared HSI techniques with multivariate classification algorithms; hence, they discriminated tea plants subjected to three different nitrogen treatments [18]. Finally, Sha et al (2019) proposed a HSI method, including multivariate techniques, to discriminate fertilized from unfertilized grasses and showed that specific wavelengths can be effectively used to assess the influence of different fertilizers on the grasses [19]. However, to the best of the authors' knowledge, no nondestructive HIS technology for FWC evaluation in OF within the visible-near-infrared (Vis/NIR) region has been developed to date.…”
Section: Introductionmentioning
confidence: 99%
“…Sha Wen et al proposed the method of combining LIBS and support vector regression (SVR) to detect three elements of nitrogen, phosphorus, and potassium in fertilizer. The results show that LIBS coupled with the least squares-support vector regression (LS-SVR) can accurately and quantitatively analyze elements in complex matrices [30]. Liwen Sheng et al applied the combination of LIBS and random forest (RF) for the identification and discrimination of iron ore.…”
Section: Introductionmentioning
confidence: 99%